Museum Sebagai Ruang Sosial: Pengelolaan Berbasis Komunitas Di Museum Purbakala Bumiayu - Adiati, Ath Thur Fithri; Tjahjono , Prasodjo (PURBAWIDYA, 2025)
The purpose of this article is to identify the forms and applications of social capital in supporting museum management, thus creating a dynamic social space at the Bumiayu Archaeological Museum. This research was conducted using qualitative methods, employing a descriptive-analytical approach. Data collection was conducted through field observations, semi-structured interviews, and literature reviews. The results show that the Bumiayu Archaeological Museum can optimize social capital well so that it can properly organize museum activities independently. The museum can seize opportunities for collaboration with various cross-sectors, both government and academic institutions, thus creating a museum social space as an educational, creative, and participatory tool.